Deep-Buried Triassic Oil-Source Correlation in the Central Junggar Basin, NW China. (11th June 2017) - Wu, Ming; Jin, Jun; Ma, Wanyun; Xiang, Baoli; Zhou, Ni; Ren, Jiangling; Cao, Jian
Abstract : Whether there is an effective deep-buried lacustrine Triassic petroleum system in the Junggar Basin, NW China, has been enigmatic and debated for a long time. Here we conduct an oil-source correlation to address this issue. Results show that the extracted bitumens from the Triassic mudstones in the central basin have distinctive stable carbon isotope and biomarker compositions compared to the Permian-sourced and Jurassic-sourced hydrocarbons, the other two recognized sources in the study area. These characteristics include δ 13 C value of - 30 . 46  ~  - 26 . 30 ‰, β -carotane/maximum n -alkane of 0.22–0.41, Pr/Ph of 1.00–1.51, C24 tetracyclic terpane/C26 tricyclic terpane of 0.43–0.96, Ts/Tm of 0.34–0.64, gammacerane/C30 hopane of 0.10–0.14, and regular steranes C27 > C28 < C29 with C29 sterane in dominance (40–50%). These suggest that the Triassic mudstones in the study area host fresh lacustrine organic matters with high input of higher plants. The Triassic-reservoired crude oils and extracts can be divided into two types. Through oil-source correlation, we infer that both type A and type B oils are derived from mixed Permian and Triassic source rocks. Linear regression analysis shows that the contribution from Triassic mudstones to type A and B oils is 67% and 31%, respectively. This implies that the deep-buried Triassic lacustrine mudstones in the Junggar Basin may have some oil-generation potential and thus might represent a new case of Triassic petroleum systems in China and deserves a more detailed and thorough study in future exploration and exploitation.